Design and Stability of Long Span Railway Arch Bridge - Josef Vican; Jozef Gocal; Jaroslav Odrobinak; Richard Hlinka (Communications, 2013)
The bow-string arch bridge across the Vah River was designed on the main Slovak railway line. Total length of the bridge is almost 451 m, while the lengths of two main spans are 124.8 m. To analyse behaviour of the bridge, spatial transformation model was developed using FEM software. The Eurocodes were applied for all verification procedures. Bridge global analysis and verification of arches against buckling is discussed in more detail. The variation of upper bracing system and its influence on out-of-plane buckling of the arches is presented. Together with an architecture point of view, a minimum load amplifier to reach the elastic instability αcr is used to estimate the suitability of the bracings.